How Many Sheep Should We Count to Stay Healthy? - Nilsson,Ludvig (2025)
Disparities in health is a common issue in society, with people of different socioeconomic backgrounds having different possibilities in terms of achieving a good level of health. Stress is a common result of this, followed by insomnia and sleep impairment amongst those who are at a socioeconomic disadvantage. In this study, data was collected from multiple Swedish databases to explore whether sleeping treatment influence the self-appreciated health of groups belonging to that of low socioeconomic status. The collected data was separated into 2 groups via a sample split to investigate whether this was the case or not. The results pointed to no such causal link and the conclusion was that addressing disparities in health is more effective at increasing public health than relying on prescribing medication.
Keywords: Benzodiazepines; Sleeping treatment; Health; Stress; Socioeconomic status